THE CORRELATION BETWEEN PERCEPTION OF LEARNING MEDIA AND LEARNING ACHIEVEMENT OF ENGLISH WITH WRITING ABILITY AT THE STUDENTS OF MTs N METRO ACADEMIC YEAR 2012/2013 - Tri Nuraini (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
In this research, the research focuses on the main problem that is on the Correlation between Perception of Learning Media and Learning Achievement of English with Writing Ability at the students of MTs N Metro Academic Year 2012/2013.The objectives of the research are (1) whether there is positive and significant correlation between perception of learning media with writing ability. (2) Whether there is positive and significant correlation between learning achievement of English with writing ability. (3) Whether there is positive and significant correlation between perception of learning media and learning achievement of English with writing ability simultaneously.The researcher uses quantitative research. The research design of this research is correlation study. The research was conducted at MTs N Metro. The sample of the research consisting of 32 students and subject of the research was students of MTs N 1 Metro at the Second Grade in Academic Year 2012/2013. The researcher uses simple random sampling as technique sampling. In collecting the data, the researcher administered questionnaire and documentation. The questionnaire consists of 20 items. To know the correlation between variables, the researcher calculated the data by using Split-half technique and formulation of Product Moment.................. After calculated the data, the result found that “r observed” = with the level of significant of “r table” 0,05 = 0,423 and the level of significant of “r table” 0,01 = 0,537. Then “r observed” with the level of significant of “r table” 5 % (0,05) = 0,423 and the level of significant of “r table” 1 % (0,01) = 0,537 that “r observed” is higher than “r table”. Therefore, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. It means that there is a positive and significant correlation between perception of learning media and learning achievement of English with writing ability.